2014
DOI: 10.1111/jace.13269
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Different Interfaces in Percolated Networks of Antimony Tin Oxide: Borosilicate Glass Composites by Impedance Spectroscopy

Abstract: Glass composites containing percolated segregated networks of conducting antimony tin oxide (ATO) nanoparticles were fabricated through the use of a hot-pressing technique, which resulted in glass microspheres deforming into faceted polyhedra with the ATO located at the edges. Once the ATO percolated, it was shown that minor changes in the processing parameters could cause drastic differences in the electrical properties (as much as 4-5 orders of magnitude in some cases). This study aims to investigate how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…R PMMA and CPE PMMA account for the edge of the network and PMMA matrix where the PMMA has separated the CNTs and therefore causes increased resistance. This model has been used previously for segregated glass composites and has been modified to suit the materials used here [22].…”
Section: Resultsmentioning
confidence: 99%
“…R PMMA and CPE PMMA account for the edge of the network and PMMA matrix where the PMMA has separated the CNTs and therefore causes increased resistance. This model has been used previously for segregated glass composites and has been modified to suit the materials used here [22].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, such modeling allowed for separation of the electrical responses from the constituent phases and interfaces, which provided additional insight into how microstructure and phase distribution were affected. The foundation for finding appropriate, physically justifiable models was based on a model previously developed for a similar material system, [18] which, upon independent verification in the current work, was found to be the most appropriate model for the ITO-borosilicate composites. The model was derived by finding circuits, which fit impedance data from tests of the isolated constituents and combinations of them, as shown in Figure 2a-d.…”
Section: Development Of Equivalent Circuit Modelsmentioning
confidence: 94%
“…This composition was chosen because its electrical response was just above the percolation threshold [17] and was expected to be very sensitive to small changes in the connectivity of the particles. [11,18] SPS was carried out using three different SPS equipment: a Thermal Technologies L.L.C model SPS 10-4, a Thermal Technologies L.L.C model SPS 25-10, and a Fuji Electronic Industrial Co., Ltd. Dr. Sinter model SPS-211Lx. These different equipment were designated as UA, TT, and GT, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This will have to be addressed in another publication where the quality of contact between the individual ITO nanoparticles can be evaluated. Previous research in our group has indicated that the quality of contact can be obtained by conducting careful impedance and dielectric spectroscopy measurements, but that falls outside the scope of this study. Additional details regarding the application of the ITO in inkjet printing and inkjet printing details are provided in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%